(3GdSjQI GdESeGYjdjIs - (3GdMGLH LYaQ Hf Ydjs
(3ChdgG (B:s
(3heG Jhajbi EdG HGddg Ydjg JhcdJ hgh QH GdYQT GdYXje s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hBNQkG hXGgQkG hHGWfkG hUdhGJg Ydi NjQ eHYhK hCcQe ehQhK s
(3QhGjI GdQGYi(B: (3eMeO Hf eMeO GdjeGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B185 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajg HMjOQ CHGO (B((3JGQjN (B2588) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdJGQjNs